PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI MASKAPAI BATIK AIR PADA BANDAR UDARA ABDURAHMAN SALEH MALANG - Ary Subiyantoro; Himawan Agung Nugroho; Anggoro Setyo Mukti (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
In this era of globalization, the aviation industry is facing increasingly fierce competition. Therefore, it is important to understand the factors that influence customer satisfaction in the context of airlines. This study aims to see how much influence service quality has on customer satisfaction of Batik Air airline passengers at Abdulrachman Saleh Malang Airport. This research was conducted at Abdulrachman Saleh Malang Airport. The type of data used in this study is primary data obtained from the distribution of questionnaires to Batik Air airline passengers at Abdulrachman Saleh Malang Airport. The research used by researchers is field research which uses a quantitative approach, namely testing or analyzing data and calculating numbers and then drawing conclusions from the testing. Based on the results of a simple regression test, it is known that service quality variables have a significant effect on customer satisfaction of Batik Air airline passengers at Abdulrachman Saleh Malang Airport. This significant effect can be seen based on the results of t-tests on independent variables of management information systems obtained a Sig value of 0.001. A probability value greater than the Sig value (0.05 greather than 0.001) can be concluded that H0 is rejected and H1 is accepted, meaning that service quality variables have a significant effect on customer satisfaction of Batik Air airline passengers at Abdulrachman Saleh Malang Airport.